Formation and development of a program-project approach within the framework of tourism industry management at the regional level - I. I. Deren; A. D. Zemlyanikina (Вестник университета)
The process of the program-project approach formation within the framework of tourism industry management both at the national and regional levels has been studied. The Vladimir Region has been chosen as the subject of the study. It has been revealed that, despite the built architecture of state programs and projects management, the process of updating and fine-tuning of this system continues, including on the basis of response to external challenges. There is still work to be done to eliminate the temporary inconsistency of target parameters of projects and programs, which results in the blurring of responsibility of management teams and inefficient spending of budget allocations at all levels of management. At present, considering the plans announced by the President of the Russian Federation in April 2024 to implement a new model of economic growth, expand the horizons of budget planning, create conditions for breakthrough disclosure of the potential of all subjects of economic policy in the tourism industry, the program-project method is an effective tool for public policy implementation. Based on the results of the assessment of the current state of the methodological basis for implementing state programs and projects in the field of tourism at the federal and regional levels, recommendations have been developed for a more accelerated and qualitative achievement of the tasks set by the President of the Russian Federation for developing the tourism industry.